Public spaces leisure in Rio Claro - SP (Brazil): Quality, distribution, and social vulnerability - De Orlando Dopp, Erik Vinicius [UNESP]; Nascimento, Wedson Guimarães [UNESP]; Goulardins, Guilherme Stefano [UNESP]; Kokubun, Eduardo [UNESP]; Nakamura, Priscila Missaki (FapUNIFESP (SciELO), 2021)
Aim: Describe public leisure spaces in a city in the state of São Paulo, associating distribution, quantity, and quality of attributes to the São Paulo Index of Social Vulnerability (IPVS). Methods: Descriptive observational study in Rio Claro (Brazil), evaluating aspects of comfort, aesthetic accessibility, and fitness for physical activity through the Physical Activity Resource Assessment (PARA) instrument in squares, parks, and habitable beds in the urban area of the municipality, using the IPVS 2010, as a basic instrument for social vulnerability. The analysis of variance (ANOVA) was adopted to verify the difference in the number of attributes and the Kruskal-Wallis test for the quality of attributes in each location evaluated according to the IPVS. Results: One hundred thirty-two squares, 2 parks, and 10 flower beds were evaluated. The ANOVA results showed that attributes related to comfort, cleanliness, aesthetics, and safety, and accessibility proved to be significant in squares and parks, while cleanliness, aesthetics, and safety showed significance in construction sites, both before the IPVS 2 - Very low vulnerability. For quality, Kruskal test Wallis identified significance in places for the practice of PA and comfort structures in parks and squares and places for the practice of PA and cleaning, aesthetics, and safety in construction sites. 92.4% of spaces are in places of low social vulnerability, with only 2.1% in places of high vulnerability. Conclusion: Our findings show poor quality of the structures, considering the attributes of comfort, cleanliness, aesthetics, and safety, and accessibility structure. In addition, most of the structures were distributed in the central areas with less social vulnerability.
Keywords: Green areas; Leisure public spaces; Physical activity; Social vulnerability